Temperature Field Analysis of Traction Linear Induction Motors Based on Field-circuit Coupling - XUE Yongpeng; WANG Shuhong; WU Pan; CHAI Jingtang (Chengshi guidao jiaotong yanjiu)
［Objective］ In urban rail transit systems, the analysis of LIM (linear induction) faces challenges due to factors such as primary core discontinuity, partial filling of the end region, and end effects. These factors complicate the analysis of electromagnetic performance, derivation of control strategy formulas, calculation of component losses, and temperature field analysis. In practical engineering applications, LIMs typically operate in conjunction with control systems, necessitating solutions to the complex problem of temperature field analysis in LIMs used in urban rail transit drive systems. ［Method］ A field-circuit coupling simulation model for an LIM vector control system is jointly built by using multiple simulation platforms, considering both transverse and longitudinal end effects. A 12 kW LIM is modeled using 3D fluid-solid coupling temperature field and finite element electromagnetic simulation methods. The finite volume method is employed for coupling the motor′s fluid and temperature fields, and the frozen rotor method is applied to account for the effects of surrounding air flow and rotor motion on the steady-state temperature rise of the motor. ［Result & Conclusion］ The accuracy of the proposed method is validated through open-loop operation experiments on a prototype. Based on the simulation results, the performance of the prototype under different traction conditions with the vector control system is analyzed. The motor exhibits fast response and stability at given speeds, demonstrating effective control. By calculating heat sources from loss curves, the temperature field distribution of the prototype is determined, providing a clear visualization of the combined effects of air flow on temperature distribution.